Moderate organic fertilizer substitution for partial chemical fertilizer improved soil microbial carbon source utilization and bacterial community composition in rain-fed wheat fields: current year - Liu, Xiaoli; Yang, Wenping; Li, Wenguang; Ali, Aamir; Chen, Jie; Sun, Min; Gao, Zhiqiang; Yang, Zhenping (Frontiers in Microbiology, 2023)
Abstract Organic manure can partially replace chemical fertilizer to improve agricultural production and reduce negative environmental impact. To study the impact of manure on soil microbial carbon sources utilization and bacterial community composition in dryland wheat field, a field experiment was conducted from 2016 to 2017 in a completely randomized block design with four treatments: the control with 100% NPK compound fertilizer of 750 kg/ha (CK), combination of 60% NPK compound fertilizer with organic manure of 150 kg/ha (FO1), 300 kg/ha (FO2), and 450 kg/ha (FO3), respectively. We investigated the yield, soil nutrients, the utilization of 31 carbon sources by soil microbes, soil bacterial community composition and function prediction at the maturation stage. Compared with CK, the FO3 and FO2 significantly increased the total nitrogen (TN), available nitrogen (AN), available phosphorus (AP), soil organic matter (SOM), ear number per hectare, grain numbers per spike, 1000-grain weight and yield. Besides, the highest AWCD (Average Well Color Development) values were in FO3. The carbohydrate and amino acids were found to be the sensitive carbon sources for soil microorganisms in different treatments. FO3 had higher utilization of β-Methyl D-Glucoside, L-Asparagine acid and Glycogen compared with other treatments, which was positively correlated with soil nutrients and wheat yield. Furthermore, significantly increased relative abundances of certain bacterial communities and KEGG orthologs were also observed in FO3. Based on these findings, we suggest FO3 to be most appropriate organic manure substitution method in dryland wheat field.